Stockholm Syndrome dalam Lirik Lagu: Analisis Hubungan Toksik dalam Kini Mereka Tahu oleh Bernadya - Rasyid, Mohammad Ricky Ramadhan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2024)
This study analyzed the lyrics of the song Kini Mereka Tahu by Bernadya through the lens of Stockholm Syndrome, a concept introduced by Dr. Nils Bejerot. The purpose of the research was to uncover the dynamics of toxic relationships reflected in the lyrics. Using a qualitative approach and content analysis method, the primary data consisted of the song's lyrics, while secondary data was gathered from reviews and relevant literature. Data analysis involved linking elements of the lyrics to the symptoms of Stockholm Syndrome. The findings revealed that the lyrics reflected key symptoms of Stockholm Syndrome, including the victim’s attempts to create an idealized narrative to justify a toxic relationship, despite being aware of its negative impact. This narrative was reinforced by a cycle of emotional manipulation that made it difficult for the victim to leave the relationship. Furthermore, the study identified the victim's growing awareness of the manipulation, which marked the beginning of emotional liberation. In conclusion, the song not only reflected individual experiences but also served as a critique of destructive relationship dynamics. This research aimed to enrich interdisciplinary discourse spanning art, psychology, and popular culture, while encouraging further studies on toxic relationships in other media.